(807) Long Term Planning التخطيط طويل الأجل - Karl-Heinz Horn (INP, 2024)
In the German Democratic Republic, prospective planning has become a key instrument of economic leadership. The growing importance of long-term scientific forecasting is due to the increasing dynamics of social processes, particularly in economic fields influenced by the ongoing scientific-technical revolution. Successful prospective planning relies on the recognition of objective social-economic laws. The social aim of long-term economic development is to meet the population's needs in material and cultural aspects. The quantitative expression of this aim is the maximum growth of available national income per capita. As the planning period extends, the determination of optimum consumption targets becomes more critical. To achieve long-term plans, forecasting, planning, and actual management must be viewed as a unified complex based on public ownership, centralized information functions, and the cooperation of the masses.